Formation of readiness for professional self-improvement of future managers - Tan Lipin (Scientific notes of the pedagogical department, 2023)
The article is devoted to the study and consideration of the process of formation of readiness for professional self-improvement in future managers. In the context of today’s dynamic business environment and high competition in the labor market, readiness for continuous self-improvement becomes extremely important to ensure the success and effectiveness of future managers. Key aspects of this process are analyzed, such as: integration of practical knowledge, development of self-study skills, involvement in active practice and reflection. Research methods incl.: analysis of documents and scientific sources; observation; comparative analysis. The article offers recomendations for effective formation of readiness for professional self-improvement of future managers in a higher education institution.